Characterisation and utilisation of sheep and goat breeds that are resistant to helminths - Baker, R.L. (Australian Centre for International Agricultural Research, 1996)
There is a large and diverse range of sheep and goat breeds in the world and some of these, particularly the indigenous tropical breeds, appear to have some unique genetic ability to resist or tolerate diseases. This paper reviews the information available on between-breed genetic variation for resistance to helminthiasis (mainly the gastrointestinal (GI) nematodes) and discusses how this genetic variation can be used in breeding porgrams. The experimental design used in nearly all the breed comparisons reviewed is inadequate. In particular, the number of animals of each breed evaluated is too small, very few studies take account of variation among sires within breeds, and how the animals are sampled is not stated. However, there are a number of sheep breeds that have been identified as resistant in a number of independent studies and these include the East Africa Red Maasai, the Florida Native, the Barbados Blackbelly and the St. Croix. There is much less evidence for breeds of goats that are resistant to GI nematodes but the indigenous tropical breeds such as the Small East African and West African Dwarf may be somewhat resistant.